2003
DOI: 10.1152/ajplung.00422.2002
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ sensitization during sustained hypoxic pulmonary vasoconstriction is endothelium dependent

Abstract: Robertson, Tom P., Philip I. Aaronson, and Jeremy P. T. Ward. Ca 2ϩ sensitization during sustained hypoxic pulmonary vasoconstriction is endothelium dependent. Am J Physiol Lung Cell Mol Physiol 284: L1121-L1126, 2003. First published February 28, 2003 10.1152/ajplung.00422. 2002The main aim of this study was to determine the effects of endothelium removal on tension and intracellular Ca 2ϩ ([Ca 2ϩ ]i) during hypoxic pulmonary vasoconstriction (HPV) in rat isolated intrapulmonary arteries (IPA). Rat IPA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 36 publications
3
55
0
3
Order By: Relevance
“…Acute hypoxia causes vasoconstriction by several mechanisms. It depolarises PASMCs by inhibiting potassium channels, leading to calcium influx as described above [17], causes the release of calcium from the sarcoplasmic reticulum and subsequent repletion through storeoperated channels [18,19], increases calcium influx into PASMCs through L-type calcium channels, independent of the membrane potential [20] and also promotes calcium sensitisation [21], thus increasing pulmonary vascular resistance [22]. Most of the calcium responsible for the increase in cytosolic calcium induced by hypoxia comes from outside the PASMC but some is released from internal stores, such as the sarcoplasmic reticulum [1].…”
Section: Discussionmentioning
confidence: 99%
“…Acute hypoxia causes vasoconstriction by several mechanisms. It depolarises PASMCs by inhibiting potassium channels, leading to calcium influx as described above [17], causes the release of calcium from the sarcoplasmic reticulum and subsequent repletion through storeoperated channels [18,19], increases calcium influx into PASMCs through L-type calcium channels, independent of the membrane potential [20] and also promotes calcium sensitisation [21], thus increasing pulmonary vascular resistance [22]. Most of the calcium responsible for the increase in cytosolic calcium induced by hypoxia comes from outside the PASMC but some is released from internal stores, such as the sarcoplasmic reticulum [1].…”
Section: Discussionmentioning
confidence: 99%
“…vascular smooth muscle; endothelium; nitric oxide; Rho kinase; temperature; endothelin-1; N -nitro-L-arginine methyl ester; Y-27632 HYPOXIC PULMONARY VASOCONSTRICTION (HPV) is thought to result from an increase in intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) in pulmonary arterial smooth muscle cells (PASMC) (37,40,48,51,52,54,56,62,72,77,82). The increased [Ca 2ϩ ] i leads in turn to calmodulin-dependent activation of myosin light chain (MLC) kinase (MLCK), MLCK-dependent phosphorylation of the 20-kDa regulatory MLC (P-MLC 20 ), P-MLC 20 -dependent activation of the actin-myosin interaction, and PASMC contraction (38,42,74,75,83).…”
mentioning
confidence: 99%
“…These results suggest that phase 2 contraction resulted from an increase in PASMC Ca 2ϩ sensitivity and that this sensitization was due to release of factors from endothelial cells, rather than direct effects of hypoxia on smooth muscle. The identities of these factors remain unknown; however, antagonists of endothelin-1 (ET-1) had no effect on phase 2 HPV in endothelium-intact IPA, suggesting that ET-1 played no role (51). Although the nitric oxide/guanylate cyclase/protein kinase G (NO/GC/PKG) transduction pathway can alter Ca 2ϩ sensitivity in pulmonary arteries (27,57), its effect on Ca 2ϩ sensitivity during acute hypoxia has not been examined.…”
mentioning
confidence: 99%
“…Nevertheless, other studies have shown that the hypoxic contraction is endothelium dependent (Aaronson et al, 2002;López-Valverde et al, 2005). Removal of the endothelium from rat pulmonary arteries does not suppress the rise in [Ca 2+ ] i during sustained hypoxia, but abolishes the hypoxic contraction, suggesting that the endothelium releases a factor that sensitises the contractile apparatus of the SMC to calcium enabling hypoxic vasoconstriction (Robertson et al, 2003).…”
Section: The Role Of the Endothelium And Et-1 In Hpvmentioning
confidence: 89%
“…Numerous controversies, however, surround the role of the endothelium and the involvement of endothelin-1 (ET-1) (Aaronson et al, 2002). Thus, while several studies show that HPV is intrinsic to PASMC, other studies indicate that the endothelium, possibly through the release of ET-1, is essential for HPV (Madden et al, 1992;Shimoda et al, 2002;Robertson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%